Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Use the function [tex]f(x) = 2x^3 - 3x^2 + 7[/tex] to complete the exercises.

[tex]\[
\begin{array}{l}
f(-1) = \hat{v} \\
f(1) = \hat{v} \\
f(2) = \hat{\imath}
\end{array}
\][/tex]


Sagot :

To evaluate the function [tex]\( f(x) = 2x^3 - 3x^2 + 7 \)[/tex] at the specified points, follow these steps:

### 1. Calculate [tex]\( f(-1) \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(-1) = 2(-1)^3 - 3(-1)^2 + 7 \][/tex]

Now evaluate this expression:
- [tex]\((-1)^3 = -1\)[/tex]
- [tex]\((-1)^2 = 1\)[/tex]
- [tex]\(2 \times (-1) = -2\)[/tex]
- [tex]\(3 \times 1 = 3\)[/tex]

Thus:
[tex]\[ f(-1) = 2(-1) - 3(1) + 7 \][/tex]
[tex]\[ f(-1) = -2 - 3 + 7 \][/tex]
[tex]\[ f(-1) = 2 \][/tex]

So, [tex]\( f(-1) = 2 \)[/tex].

### 2. Calculate [tex]\( f(1) \)[/tex]:
Substitute [tex]\( x = 1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(1) = 2(1)^3 - 3(1)^2 + 7 \][/tex]

Now evaluate this expression:
- [tex]\((1)^3 = 1\)[/tex]
- [tex]\((1)^2 = 1\)[/tex]
- [tex]\(2 \times 1 = 2\)[/tex]
- [tex]\(3 \times 1 = 3\)[/tex]

Thus:
[tex]\[ f(1) = 2(1) - 3(1) + 7 \][/tex]
[tex]\[ f(1) = 2 - 3 + 7 \][/tex]
[tex]\[ f(1) = 6 \][/tex]

So, [tex]\( f(1) = 6 \)[/tex].

### 3. Calculate [tex]\( f(2) \)[/tex]:
Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 2(2)^3 - 3(2)^2 + 7 \][/tex]

Now evaluate this expression:
- [tex]\((2)^3 = 8\)[/tex]
- [tex]\((2)^2 = 4\)[/tex]
- [tex]\(2 \times 8 = 16\)[/tex]
- [tex]\(3 \times 4 = 12\)[/tex]

Thus:
[tex]\[ f(2) = 2(8) - 3(4) + 7 \][/tex]
[tex]\[ f(2) = 16 - 12 + 7 \][/tex]
[tex]\[ f(2) = 11 \][/tex]

So, [tex]\( f(2) = 11 \)[/tex].

### Summary:
[tex]\[ \begin{array}{l} f(-1) = 2 \\ f(1) = 6 \\ f(2) = 11 \end{array} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.